Health Care Surrogacy Laws Do Not Adequately Address the Needs of Minors - Gandhi, Rupali (The Hastings Center report, 2020)
A couple and their five-year-old daughter are in a car accident. The parents are not expected to survive. The child is transported to a children's hospital, and urgent treatment decisions must be made. Whom should the attending physician approach to make decisions for the child? When such cases arise in, for example, the hospitals where we work, the social worker or chaplain is instructed to use the Illinois Health Care Surrogacy Act as a guidepost to identify a decision-maker. But in our state and the country overall, the limitations of such statutes leave hospital workers to make a judgment call among friends, family, and clergy who may come forward. While surrogate decision-making statutes comprehensively address surrogate decision-makers for adults, a patchwork of laws—permanency statutes, kinship provider statutes, standby guardianship statutes, and, in some cases, surrogate decision-making statutes—provide variable decision-making pathways for children.